A Digital Home-Based Health Care Center for Remote Monitoring of Side Effects During Breast Cancer Therapy: Prospective, Single-Arm, Monocentric Feasibility Study - Hübner, Hanna; Wurmthaler, Lena; Goossens, Chloe; Ernst, Mathias; Mocker, Alexander; Krückel, Annika; Kallert, Maximilian; Geck, Jürgen; Limpert, Milena; Seitz, Katharina; Rübner, Matthias; Kreis, Philipp; et al. (JMIR Cancer, 2025)
Background: The introduction of oral anticancer therapies has, at least partially, shifted treatment from clinician-supervised hospital care to patient-managed home regimens. However, patients with breast cancer receiving oral cyclin-dependent kinase 4/6 inhibitor therapy still require regular hospital visits to monitor side effects. Telemonitoring has the potential to reduce hospital visits while maintaining quality care. Objective: This study aims to develop a digital home-based health care center (DHHC) for acquiring electrocardiograms (ECGs), white blood cell (WBC) counts, side effect photo documentation, and patient-reported quality of life (QoL) data. Methods: The DHHC was set up using an Apple Watch Series 6 (ECG measurements), a HemoCue WBC DIFF Analyzer (WBC counts), an iPhone SE (QoL assessments and photo documentation), a TP-Link M7350-4G Wi-Fi router, and a Raspberry Pi 4 Model B. A custom-built app stored and synchronized remotely collected data with the clinic. The feasibility and acceptance of the DHHC among patients with breast cancer undergoing cyclin-dependent kinase 4/6 inhibitor therapy were evaluated in a prospective, single-arm, monocentric study. Patients (n=76) monitored side effects—ECGs, WBC counts, photo documentation, and QoL—at 3 predefined time points: study inclusion (on-site), day 14 (remote), and day 28 (remote). After the study completion, patients completed a comprehensive questionnaire on user perception and feasibility. Adherence to scheduled visits, the success rate of the data transfer, user perception and feasibility, and the clinical relevance of remote measurements were evaluated. Results: Mean adherence to the planned remote visits was 63% on day 14 and 37% on day 28. ECG measurements were performed most frequently (day 14: 57/76, 75%; day 28: 31/76, 41%). The primary patient-reported reason for nonadherence was device malfunction. The expected versus the received data transfer per patient was as follows: ECGs: 3 versus 3.04 (SD 1.9); WBC counts: 3 versus 2.14 (SD 1.14); QoL questionnaires: 3 versus 2.5 (SD 1.14); and photo documentation: 6 versus 4.4 (SD 3.36). Among patients, 81% (55/68) found ECG measurements easy, 82% (55/67) found photo documentation easy, and 48% (33/69) found WBC measurements easy. Additionally, 61% (40/66) of patients felt comfortable with self-monitoring and 79% (54/68) were willing to integrate remote monitoring into their future cancer care. Therapy-induced decreased neutrophil count was successfully detected (P<.001; mean baseline: 4.3, SD 2.2, ×109/L; on-treatment: 1.8, SD 0.8, ×109/L). All-grade neutropenia and corrected QT interval prolongations were detected in 80% (55/68) and 2% (1/42) of patients, respectively. Conclusions: Adherence to scheduled remote visits was moderate, with nonadherence primarily attributed to device-related complications, which may have also affected the success rate of data transfer. Overall, patients considered remote monitoring useful and feasible. The prevalence of reported adverse events was comparable to existing literature, suggesting clinical potential. This initial feasibility study highlights the potential of the DHHC.
CRIS-Team Scopus Importer:2025-05-30
Keywords: breast cancer; CDK4/6 inhibitor; cyclin-dependent kinase 4/6 inhibitor; digital medicine; mobile phone; remote monitoring; telehealth

Can Chat-GPT read and understand guidelines? An example using the S2k guideline intrauterine growth restriction of the German Society for Gynecology and Obstetrics - Psilopatis, Iason; Bader, Simon; Krückel, Annika; Kehl, Sven; Beckmann, Matthias; Emons, Julius (Archives of Gynecology and Obstetrics, 2024)
Purpose: To investigate the capacity of chat-generative pre-trained transformer (Chat-GPT) to understand the S2k guideline of the German Society for Gynecology and Obstetrics on intrauterine growth restriction. Methods: The German-language free Chat-GPT version was used to test the ability of Chat-GPT to understand the definition of small for gestational age and intrauterine growth restriction, to indicate the correct time and place of delivery and to evaluate ist ability to recommend a spontaneous delivery versus a primary caesarean section in accordance with the guideline recommendations. In order to objectively evaluate the suggestions a simple three-color ‘traffic light’ evaluation system was employed. Results: Almost all Chat-GPT’s suggestions in the context of definition of small for gestational age/intrauterine growth restriction as well as correct time of delivery were adequate, whereas more than half of the suggestions made in terms of correct delivery mode needed reformulation or even correction. Conclusion: Chat-GPT appears to be a valuable form of artificial intelligence that could be integrated into everyday clinical practice.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Chat-GPT; Growth; Guideline; Intrauterine; Restriction

Clinical and Surgical Evaluation of Sentinel Node Biopsy in Patients with Early-Stage Endometrial Cancer and Atypical Hyperplasia - Pöschke, Patrik; Gaß, Paul; Krückel, Annika; Keller, Katharina; Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Emons, Julius (Geburtshilfe und Frauenheilkunde, 2024)
Introduction The medical and surgical treatment of endometrial cancer (EC) is evolving toward a more patient-centered and personalized approach. The role of laparoscopic sentinel node biopsy (SNB) for early-stage EC is unclear, and very few data are available for atypical endometrial hyperplasia (AEH). The present study investigated the effectiveness of SNB combined with laparoscopic hysterectomy in patients with early-stage EC and AEH. Patients and Methods This was a retrospective, single-center cohort study for the period from January 2018 to December 2023. A total of 102 patients with atypical hyperplasia (n = 20) and early-stage EC (n = 82) findings on diagnostic curettage underwent pelvic sentinel node biopsy during the final operation. Results Eleven patients (55%) who had initially been diagnosed with AEH were found to have EC in the final pathology report. No lymph node metastases were detected in patients who had initially been diagnosed with AEH; a 3.6% rate of positive SNBs was found in patients with EC. Changes in tumor grade occurred in 31.3% of the patients and changes in FIGO stage in 33%. Bilateral sentinel node (SN) mapping was successful in 94.1% of the patients. The postoperative outcomes were comparable to those of routine clinical practice without SNB. Conclusions SNB can be safely offered to patients who have precursor lesions and early-stage EC without notably extending surgical times or increasing postoperative morbidity. This approach can be considered and is safe for patients diagnosed with AEH, but it appears to have a rather small impact on these patients.
CRIS-Team Scopus Importer:2024-06-14
Keywords: atypical endometrial hyperplasia; endometrial cancer; indocyanine green; sentinel node biopsy; surgery

Evaluation of ChatGPT’s Potential in Tailoring Gynecological Cancer Therapies - Krückel, Annika; Brückner, Lena; Psilopatis, Iason; Fasching, Peter; Beckmann, Matthias; Emons, Julius (In Vivo, 2024)
Background/Aim: Demographic change and increasing complexity of therapy decisions lead to a growing burden on the healthcare system, necessitating efforts to simplify and enhance the efficiency of patient care. The present study evaluates ChatGPT’s ability to provide therapy recommendations for gynecological malignancies that are both in line with the local guidelines and individually tailored to the patient. Patients and Methods: Sixteen patients with endometrial, cervical, and ovarian cancer who were treated in the gynecological clinic of the University Hospital Erlangen from January 2022 to August 2023 were included in the analysis. Data collected within clinical routine care were communicated to the chat-based AI model ChatGPT (version 3.5). ChatGPT’s performance generating treatment plans were evaluated using an answer scoring system and descriptive analysis. Results: According to the answer scoring system [range: –1 point (minimum) to 2 points (maximum)], ChatGPT demonstrated a good potential in generating therapy recommendations with an average score of 0.75 points for patients with ovarian cancer, 0.7 points for cervical and 1.5 points for endometrial cancer patients. The most common deductions in points were about incomplete therapy recommendations, whereas contraindicated treatment modalities were rarely suggested. Individual patient characteristics were regularly considered by ChatGPT. ChatGPT reliably indicated aftercare and provided detailed information on preventive measures as well as supportive treatment. Conclusion: ChatGPT is a promising tool for the generation of therapy suggestions for gynecological carcinomas with high flexibility in response to individual patient differences. At the current state, however, ChatGPT is not suitable for replacing expert panels.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Artificial intelligence; cervical cancer; ChatGPT; endometrial cancer; ovarian cancer

Therapy of early breast cancer: current status and perspectives - Tauber, Nikolas; Amann, Niklas; Dannehl, Dominik; Deutsch, Thomas M.; Dimpfl, Moritz; Fasching, Peter; Hartkopf, Andreas; Heublein, Sabine; Hilmer, Lisbeth; Hörner, Manuel; Krawczyk, Natalia; Krückel, Annika; et al. (Archives of Gynecology and Obstetrics, 2025)
Medical advancements in breast cancer are truly remarkable. Especially in recent years, numerous new therapeutics have been approved and surgical strategies have been de-escalated for specific patient groups. In the therapeutic setting, CDK4/6 inhibitors as oral maintenance therapy in early breast cancer and immune checkpoint inhibitors (Pembrolizumab) for triple-negative breast cancer (BC) are noteworthy. In the surgical field, prospective randomized controlled trials have currently explored the possibility to deescalate axillary surgery by omitting sentinel lymph node excision (INSEMA, SOUND). As a result, there have been significant improvements in prognosis and a reduction in surgical morbidity for patients. Many exciting trials are underway, and it remains to be seen whether antibody–drug conjugates beyond trastuzumab emtansine, will find their way into the treatment lines for early-stage BC. Furthermore, the integration of artificial intelligence in both diagnostics and treatment recommendation evaluation is a promising area with great potential.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Early breast cancer; Future perspectives; HER2-positive; Hormone-receptor positive; Surgical de-escalation; Triple-negative

The role of artificial intelligence in gynecologic and obstetric emergencies - Psilopatis, Iason; Heindl, Felix; Cupisti, Susanne; Fischer, Ulrike; Kohlmann, Valentina; Schneider, Michael; Bader, Simon; Krückel, Annika; Emons, Julius (European Journal of Obstetrics Gynecology and Reproductive Biology, 2025)
Objective: To investigate the potential of artificial intelligence (AI) in emergency medicine, focusing on its utility in triaging and managing acute gynecologic and obstetric emergencies. Methods and Materials: This feasibility study assessed Chat-GPT's performance in triaging and recommending management interventions for gynecologic and obstetric emergencies, using ten fictive cases. Five common conditions were modeled for each specialty. Chat-GPT was tasked with proposing triage classifications and providing immediate management recommendations. Human experts independently reviewed each case, classified triage categories, and proposed management. Following this, experts evaluated Chat-GPT's recommendations, rating the AI's responses on accuracy and clinical applicability. Results: Chat-GPT's recommendations demonstrated high concordance with human evaluators. Chat-GPT's triage classifications matched those of human experts in most cases, though minor discrepancies in urgency ratings were observed. The AÍs suggestions were mostly rated as “very good” to “excellent.” While Chat-GPT consistently delivered appropriate responses, some human evaluators noted slight differences in perceived urgency. Conclusions: This study highlights Chat-GPT's potential as a clinical support tool in emergency medicine. Chat-GPT provided structured, evidence-based recommendations comparable to those of experienced clinicians, especially for high-stakes gynecologic and obstetric emergencies. Although encouraging, these results highlight the value of utilizing AI in addition to human knowledge, as variations in urgency ratings and management nuances highlight the necessity of human supervision in crucial decision-making.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Artificial intelligence; Clinical practice; Emergency; Gynecologic; Obstetric

Update Breast Cancer 2024 Part 1 - Expert Opinion on Advanced Breast Cancer - Würstlein, Rachel; Kolberg, Hans Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Schütz, Florian; Fasching, Peter; Janni, Wolfgang; Witzel, Isabell; Thomssen, Christoph; Krückel, Annika; Belleville, Erik; et al. (Geburtshilfe und Frauenheilkunde, 2024)
Clinical evidence is interpreted based on clinical studies and personal experience which can lead to different interpretations of data. This makes the opinions issued by panels of experts such as the Advanced Breast Cancer Panel which convened in November 2023 for the seventh time (ABC7) particularly important. At the conference, current issues around advanced breast cancer were evaluated by an international team of experts.In 2023 the data on CDK4/6 inhibitors was so extensive that the answers to questions about the sequencing of therapy and the potential use of chemotherapy as an alternative therapy were relatively clear. Moreover, data on antibody drug conjugates which provides a good overview of their uses is available for all molecular subtypes.Some therapeutic settings, including patients with brain metastases or leptomeningeal disease, older patients, locally advanced breast cancer and visceral crises, continue to be particularly important and were discussed in structured sessions. The scientific context of some of the topics discussed at ABC7 is presented and assessed here.
CRIS-Team Scopus Importer:2024-06-14
Keywords: antibody drug conjugate; breast cancer; chemotherapy; endocrine therapy; metastatic

Uterus didelphys and cervical cancer: A case report - Krückel, Annika; Saatze, Miriam; Behrens, Annika; Beckmann, Matthias; Pöschke, Patrik; Emons, Julius (Gynecologic Oncology Reports, 2024)
Background: Deficiencies in the merging process of the paramesonephric ducts as part of the embryonal development lead to anomalies of the uterus, cervix, fallopian tubes and proximal vagina (Müllerian malformations). The co-occurrence with cervical cancer is rare and there are no standardized protocols for managing urogenital anomalies in the realm of oncologic treatment for gynecological carcinomas. Case report: A symptom-free 41-year-old woman (gravida 0) presented at our clinic with an externally obtained AGC-FN (atypical glandular cells – favor neoplastic) finding in the Papanicolaou (Pap) smear test and persistent positivity for human papillomavirus (HPV) type 16. Sample biopsies from the portio vaginalis uteri confirmed a cervical intraepithelial neoplasia (CIN) III/ high grade squamous intraepithelial lesion (HSIL), invasive carcinoma could not be ruled out. The examinations revealed the incidental finding of a uterus didelphys and renal agenesis on the left side. After cervical conization, the patient was diagnosed with squamous cell carcinoma of the cervix. Guideline-compliant treatment with laparotomic hysterectomy according to Piver type II following a staging laparoscopy with sentinel lymphadenectomy was performed. A customized protocol was used for the indocyanine green (ICG) injection as part of the sentinel lymph node examination, tailored to the patient's anatomical characteristics. Discussion: Müllerian malformations may impede detection and treatment of gynecological carcinomas. Individualized therapy planning is necessary to meet the anatomical peculiarities of the genital anomaly. In instances of concomitant urinary tract anomalies, protective measures are imperative to safeguard normal kidney function. Conclusion: The current case demonstrates the successful implementation of guideline-compliant therapy for early-stage cervical cancer in an individual with Müllerian malformation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Cervical cancer; Urogenital anomaly; Uterus didelphys